Aplicações práticas do modelo PhenoGlad e o efeito da deficiência hídrica na cultura do gladíolo - Becker, Camila Coelho (2019)
The objectives of this thesis were (i) to develop a climate risk zoning for gladiolus in the predicted end-century climate change scenarios in Rio Grande do Sul; (ii) to apply a crop forecasting methodology to predict the date of harvest of gladiolus; (iii) to understand how water deficit affects gladiolus growth and development (iv) to understand how occur the decline in transpiration and leaf growth in a drying soil for different cultivars of gladiolus on diferent developmental stages. The PhenoGlad model was used to determine the recommended periods for gladiolus planting throughout the year in RS under three climate change scenarios (RCP2.6, RCP4.5 and RCP8.5). The model was run for daily planting dates (01January to 31 December) and different crop development cycles. PhenoGlad has also been used to predict the harvest forecast of flower stems using historical weather data. Two field experiments were conducted with four cultivars of gladiolus submitted to two irrigation treatments: irrigated and non-irrigated. Three experiments were carried out in pots, with four gladiolus cultivars in different development stages and two water regimes: without water deficit and with water deficit. FATS, transpiration and leaf growth were measured daily. In both experiments, the phenological development was evaluated daily and, at the time of harvest point, the quantitative parameters of the floral stems were measured. Warmer regions such as Uruguaiana and Iraí have the shortest recommended planting period throughout the year in the three climate scenarios, and planting between August and December is not recommended due to the higher chance of damage from high temperatures. Colder regions such as Bom Jesus will be favored in climate change scenarios. To meet the demand for gladiolus during the warmer periods of the year, techniques will need to be developed to reduce damage from high temperatures in the crop, such as more tolerant cultivars or the use of shading screens on the crop. In the first three forecasts in RS, the RMSE ranged from 7 to 4.5 days. In SC, the RMSE ranged from 5.5 to 3.4 days. These errors are acceptable from a practical point of view because they are predicted about 45 days before harvest. With this forecasting methodology, farmers can know in advance about the chances of harvesting at the desired time. The duration of the gladiolus development cycle was longer in the non-irrigated treatment. The water deficit also affects the quality of the flower produced, due to the lower plant growth, however, it does not affect the dry mass partition. Therefore, supplemental irrigation in gladiolus is essential for the production of quality floral stems. The FTSW threshold for NTR is higher when it occurs near the reproductive phase and the floral stems produced are of inferior quality. When the water deficit occurs during the vegetative phase, the rate of leaf appearance occurs more slowly, delaying the harvesting point of the flower stems.